Important issues related to the official language of India - Н.A. Ocпaн; Д.М. Кoкeeвa (Journal of Oriental Studies, 2020)
Popularization and implementation of the state language cannot be successful without a clear and scientific analysis of the general language situation. Sociological and sociolinguistic monitoring provides adjustments in language policy that reflect the pace of language processes and their regional differentiation in terms of demographic, social and ethnic dimensions. It is necessary to take measures to further improve the legal framework in the field of language policy for the implementation of the state language development program. Today, many comprehensive studies and assessments of the language situation and implementation of language policy in India are conducted by domestic and foreign scientists. This article analyzes information about official events in the state language in the Republic of India. The article considers the need to develop legal acts on the development of the state language, official speeches of authorized persons and the preparation of official documents in the state language, the state of education in the country, the language situation of other Indian languages. Key words: official language, language situation, Hindi language, Language policy, education system.